Research progress of stem cells in the treatment of atherosclerosis - Shi, Peifei; Ren, Chao; Tong, Hongjie (Frontiers in Cell and Developmental Biology, 2026)
Atherosclerosis (AS) is the primary pathological basis for the disability and mortality rates of global cardiovascular diseases. Its core characteristics are abnormal deposition of blood vessel wall lipids, chronic inflammatory activation, and vascular structural remodeling, which ultimately lead to acute cardiovascular and cerebral vascular events such as coronary heart disease and cerebral infarction. Existing treatment methods, such as statins and interventional interventions, can only delay disease progression and cannot reverse the pathological damage to blood vessels that has already occurred. Stem cells provide a novel strategy for the targeted therapy of AS due to their multi-directional differentiation potential, immune regulatory ability, and tissue repair properties. This review systematically reviews the research progress of stem cells in the treatment of AS in recent years, focusing on the mechanism of the main cell types such as mesenchymal stem cells (MSCs), induced pluripotent stem cells (iPSCs), and endothelial progenitor cells (EPCs), including regulating lipid metabolism, inhibiting inflammatory reaction, repairing vascular endothelium, and stabilizing atherosclerotic plaque. This study summarizes the key evidence from animal experiments and clinical trials in 2023–2025; analyzes core challenges such as low homing efficiency, short survival time, and the risk of immune rejection of stem cells; and proposes optimization strategies such as gene modification, biomaterial carriers, and combination therapy. Finally, the application prospects of single-cell sequencing, organoid models, and precision delivery systems in promoting the clinical translation of stem cells are discussed, with specific implementation paths being supplemented: single-cell sequencing can analyze the heterogeneity of stem cells in the AS lesion microenvironment (e.g., subtype differentiation differences of MSCs under hypoxic conditions) to screen high-activity stem cell subpopulations; vascular organoids constructed from patient-derived iPSCs can simulate the in vivo lipid deposition-inflammatory microenvironment to evaluate stem cell therapeutic effects; and precision delivery systems can enhance lesion targeting via ligand modification (e.g., anti-VCAM-1 antibody-modified PLGA carriers), thus providing theoretical basis and research directions for the disease modification therapy of AS.